Centro intercultural indígena en Piendamó, Cauca (2021)
The present work is located in the municipality of Piendamó - Cauca, because in this municipality the largest meeting point of the indigenous communities in the entire department is located, this is the governorate of the indigenous reservation La María, which is located in the village Maria outside the reservation in a lot belonging to this. Since a large part of their organization and resistance depends on the capacity of the members of the reservations to meet and mobilize, and the lack of cultural spaces to transmit knowledge. The imminent need arises to design and build a space that allows the development of mass activities of decision-making, political mobilization and recreational, festive or ceremonial activities and transmission of knowledge. For this reason, this work focuses on the design of an indigenous intercultural Center that integrates the concept of ethnicity and worldview into its architecture, providing a place with the optimal characteristics for the development of its meetings, such as the offer of services, shelter and food. , sanitary; This prevents problems such as the unhealthy conditions that currently occur due to the massive attendance of people accompanied by the fact that some stay without the infrastructure to receive them.